Pengaruh Ukuran Perusahaan Terhadap Zakat Bank Syariah Dengan ISR Sebagai Variabel Moderasi - Dewi Kusuma Wardani; Nur Anita Chanda Putry; Aprillia Dwi Cahyani Puri (Universitas Widyatama, 2022)
This study aims to analyze the moderation of Islamic Social Reporting (ISR) on the effect of firm size on corporate zakat. This study uses sharia commercial banks as research samples taken from 2014-2020. This data was obtained from the OJK and BI websites. This study uses a purposive sampling technique with 38 observations from six sharia commercial banks and uses a quantitative approach with secondary data from the annual reports of sharia commercial banks. The method used in testing this data using simple linear regression analysis and MRA test. The results of this study indicate that the firm size variable has a positive effect on corporate zakat. This study also shows that the Islamic Social Reporting variable cannot moderate the relationship between company size and company zakat